Trend Analysis and Predicting Covid-19 Pandemic of The First 2022, in Ethiopia - Aragaw Asfaw (Indonesian Journal of Applied Research (IJAR), 2022)
COVID-19, Caused by the novel coronavirus was first known officially in Wuhan City, China and spreads worldwide, including Ethiopia. Globally, as of 13 March 2022, more than 455 million confirmed cases and over 6 million deaths were reported. The aim of the study was to explore the trend of total cases and total deaths of COVID-19 using ARIMA models and predicting the occurrence of COVID-19 cases and deaths in 1st 2022 in Ethiopia. The data were collected from the official website of the Data on COVID-19 by “Our World in Data”. The data on 1st 2022 in Ethiopia is extracted for modeling ARIMA. Model identification, parameter estimation and model diagnosis were performed. Tests are at alpha 0.05. A total cases of COVID-19 about 469170 and total deaths 7485 respectively, were observed up to March 12 2022. ARIMA (0,2,1) for total death and ARIMA (0,2,4) for total case were estimated by Expert Modeler using SPSS 20 software. The trend shows an increasing pattern on a daily basis in the number of total cases and total deaths. The 70-day forecast showed a gradual increasing trend in total cases and total deaths of COVID-19 in Ethiopia by 1st 2022. This finding used as a decision-making tool to health interventions and decrease the spread of COVID-19 virus.